Achieving good outcomes in foster care: a personal perspective on research across contexts and cultures. - June Thoburn (Social Work and Society)
This paper presents a brief synthesis of learning from recently published European foster care research, focussing especially on papers given at the 2015 Siegen foster care research conference. It considers how a range of output and outcome measures have been used by researchers using a range of methodologies. It uses cross-national data on children in foster care as a basis for considering how different high income countries have both similar and different aims for their foster care services. Taking a personal perspective informed by the author's experiences of collaborative research, it then gives examples of how differences in aims may impact on the types of research studies in different countries, looking at research on foster care services as a whole, and research on foster carers, foster children and birth relatives.